Dialysis Disequilibrium Syndrome and Cerebellar Herniation with Successful Reversal Using Mannitol. (25th August 2020) - Curtis, Anna; Lamb, Christian; Rao, Hussain; Williams, Andrew; Patel, Amit
Abstract : Dialysis disequilibrium syndrome (DDS) is a morbid but rare complication of dialysis. Feared sequalae of this diagnosis are brain herniation and death. This report presents a patient who was diagnosed with DDS with subsequent tonsillar herniation shown on imaging with complete resolution of clinical signs and symptoms, as well as imaging findings of herniation after prompt initiation of intravenous mannitol. This is the first known case of reversal and survival of DDS-induced tonsillar herniation using mannitol.